LBA10Phase III PAOLA-1/ENGOT-ov25 trial: Olaparib plus bevacizumab (bev) as maintenance therapy in patients (pts) with newly diagnosed, advanced ovarian cancer (OC) treated with platinum-based chemotherapy (PCh) plus bev. (24th November 2019) - Fujiwara, K; Harter, P; Leary, A; Perol, D; Pignata, S; González-Martín, A; Petru, E; van Nieuwenhuysen, E; Colombo, N; Mäenpää, J; Selle, F; de Gregorio, N; et al.
Abstract: Background: PAOLA-1/ENGOT-ov25 (NCT02477644) is the first phase III trial to evaluate the efficacy and safety of a PARP inhibitor with bev as first-line (1L) maintenance therapy for advanced OC, regardless of BRCA1/2 mutation (BRCAm) status. Methods: PAOLA-1 is a randomized, double-blind, international phase III trial. Eligible pts had newly diagnosed, FIGO stage III–IV, high-grade serous or endometrioid OC, fallopian tube or primary peritoneal cancer. Pts had received standard PCh plus bev and were in clinical complete or partial response. Pts were randomized (2:1) to olaparib tablets (300 mg bid for up to 24 months [m]) plus bev (15 mg/kg, d1, q3w, for 15 m including when combined with PCh) or placebo (pbo) plus bev, stratified by 1L treatment outcome and tumour BRCAm status. The primary endpoint was investigator-assessed progression-free survival in the intent-to-treat population (PFS; modified RECIST v1.1). Results: 537 pts were randomized to olaparib plus bev and 269 to pbo plus bev. Pt characteristics were well balanced. Median follow-up was 22.7 m in the olaparib arm and 24.0 m in the pbo arm. PFS was significantly increased in the olaparib arm. PFS2 is immature. Grade ≥3 AEs were reported by 57% vs 51% of olaparib and pbo pts; the most common were hypertension (19% vs 30%) and anaemia (17% vs < 1%). There were five treatment emergent AEs of death (olaparib, n = 1; pbo, n = 4). Olaparib and pbo dose interruptions, reductions and discontinuations occurred in 54% vs 24%, 41% vs 7% and 20% vs 6% of pts, respectively. There was no clinically meaningful difference in health-related quality of life. Conclusions: Addition of olaparib to bev maintenance therapy following 1L PCh plus bev led to a statistically significant and clinically meaningful PFS benefit in pts with advanced OC. The PFS benefit in pts with a tBRCAm and in HRD-positive pts was substantial. Clinical trial identification: NCT02477644, release date 28 February 2019. Editorial acknowledgement: Laura Smart, MChem, from Mudskipper Business Ltd, funded by ARCAGY Research, AstraZeneca and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (MSD). Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: K. Fujiwara: Honoraria (self), Research grant / Funding (self): AstraZeneca; Honoraria (self), Research grant / Funding (institution): Chugai Roche; Honoraria (self): Zeria; Honoraria (self): Taiho; Honoraria (self): Nihon Kayaku; Honoraria (self): Kyowahakko Kirin; Honoraria (self): Janssen; Honoraria (self): Daiichi Sankyo; Advisory / Consultancy, Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy, Research grant / Funding (institution): Eisai; Research grant / Funding (institution): Kaken. P. Harter: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self): Sotio; Honoraria (self), Advisory / Consultancy: Tesaro; Honoraria (self): Stryker; Honoraria (self): Zai Lab; Honoraria (self), Advisory / Consultancy: MSD/Merck; Advisory / Consultancy: Lilly; Advisory / Consultancy: Clovis; Advisory / Consultancy: Immunogen. A. Leary: Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy: Clovis; Advisory / Consultancy, Travel / Accommodation / Expenses: Tesaro; Advisory / Consultancy, Research grant / Funding (institution): Gamamabs; Advisory / Consultancy: Gridstone; Advisory / Consultancy: Biocad; Advisory / Consultancy: Seattle Genetics; Research grant / Funding (institution): Merus; Research grant / Funding (institution): Inivata; Research grant / Funding (institution): Sanofi; Travel / Accommodation / Expenses: Roche. D. Perol: Honoraria (self), Travel / Accommodation / Expenses: Roche; Honoraria (self), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self): Eli Lilly; Honoraria (self): Ipsen; Honoraria (self): Novartis; Honoraria (self): BMS. S. Pignata: Honoraria (self), Research grant / Funding (institution): Roche; Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Research grant / Funding (institution): MSD; Honoraria (self): Pfizer; Honoraria (self): Incyte; Honoraria (self): Novartis; Honoraria (self): PharmaMar; Honoraria (self): Clovis; Honoraria (self): Tesaro. A. González-Martín: Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony: Tesaro; Advisory / Consultancy: Clovis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Immunogen; Advisory / Consultancy, Speaker Bureau / Expert testimony: PharmaMar; Advisory / Consultancy, Speaker Bureau / Expert testimony: MSD; Advisory / Consultancy: Genmad; Advisory / Consultancy: Novartis. E. Petru: Honoraria (institution), Advisory / Consultancy: AstraZeneca; Honoraria (institution), Advisory / Consultancy: Roche; Honoraria (institution), Advisory / Consultancy: Tesaro; Honoraria (institution), Advisory / Consultancy: Merck-Sharp Dohme. N. Colombo: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: PharmaMar; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Tesaro; Honoraria (self), Advisory / Consultancy: Clovis; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Biocad; Honoraria (self), Advisory / Consultancy: Takeda. J. Mäenpää: Honoraria (self), Travel / Accommodation / Expenses: Roche; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Tesaro; Advisory / Consultancy: Clovis; Advisory / Consultancy: MSD. F. Selle: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Honoraria (self), Travel / Accommodation / Expenses: MSD France; Honoraria (self): PharmaMar; Honoraria (self), Travel / Accommodation / Expenses: Tesaro; Honoraria (self): Clovis; Honoraria (self), Travel / Accommodation / Expenses: AstraZeneca. N. de Gregorio: Advisory / Consultancy: Roche; Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy, Travel / Accommodation / Expenses: Tesaro; Advisory / Consultancy: Clovis; Advisory / Consultancy: PharmaMar. D. Lorusso: Honoraria (self), Advisory / Consultancy: Merck; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Travel / Accommodation / Expenses: Tesaro; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Clovis; Advisory / Consultancy: Immunogen; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: PharmaMar; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Officer / Board of Directors: GCIG. E.M. Guerra Alia: Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Advisory / Consultancy: Clovis; Advisory / Consultancy: AstraZeneca; Speaker Bureau / Expert testimony: GEICO; Speaker Bureau / Expert testimony: Senpe; Travel / Accommodation / Expenses: Baxter. C. Lefeuvre-Plesse: Advisory / Consultancy: AstraZeneca; Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Novartis; Travel / Accommodation / Expenses: Pfizer. P. Buderath: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Research grant / Funding (institution): DFG; Research grant / Funding (institution): Deutsche Krebsgesellschaft; Travel / Accommodation / Expenses: PharmaMar. A. Lortholary: Honoraria (self): AstraZeneca; Honoraria (self): Tesaro. A. Burges: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Tesaro; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca. E. Pujade-Lauraine: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Tesaro; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Advisory / Consultancy: Clovis; Advisory / Consultancy: Genmab; Advisory / Consultancy: Incyte; Advisory / Consultancy: MSD; Advisory / Consultancy: Pfizer. I.L. Ray-Coquard: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Advisory / Consultancy: Clovis; Honoraria (self), Advisory / Consultancy: Tesaro; Honoraria (self), Advisory / Consultancy: PharmaMar; Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Advisory / Consultancy: Genmab; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy: Pfizer.